Conjunctive photoluminescence enhancement through plasmonic and photonic band-gap pathways in a chiral self-assembled system - Baral, Marlin; Krishna Prasad, S.; Bhat, Sachin A.; Nayak, Rashmi A.; Yelamaggad, C. V. (ChemPhotoChem, 2020)
We describe two parallel pathways for enhancing the intrinsic photoluminescence of an organic emitter dispersed in a liquid crystal (LC) medium. The pathways have independent origins: (i) Metal enhanced fluorescence (MEF) incorporating gold nanoparticles having an organic shell of pro-mesogenic cholesterol esters; and (ii) Matching the photonic band gap (PBG) due to the helical structure in a self-assembled chiral system with the excitation wavelength. This unprecedented combination of both pathways achieves a level of photoluminescence exceeding the sum of the contribution from the individual methods. This conjunctive protocol results in an overall enhancement by a factor of 37 between the emitter dispersed in a non-chiral LC and that appealing to both MEF and PBG pathways. Circular polarized luminescence measurements also show that this protocol helps in effective discrimination of chiral light achieving a large dissymmetry factor whose magnitude (+0.33) is comparable to the highest recorded to date. Electric field switching between two states is also shown to result in appreciable fluorescence modulation. Being generic in nature the protocol employed can be adapted to a variety of situations with the large magnitude as well the modulation level suitable for applications such as biosensors, various analyte detection, and other photonic devices.
Keywords: chirality; circularly polarized luminescence; liquid crystals; photonic band-gap; plasmonics

Boron- and oxygen-doped π-extended helical nanographene with circularly polarised thermally activated delayed fluorescence - Venugopal, Geethu; Kumar, Viksit; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Khan, Abujunaid; Gonnade, Rajesh; Kumar, Jatish; Santhosh Babu, Sukumaran (Chemistry-A European Journal, 2024)
Helical nanographenes have garnered substantial attention owing to their finely adjustable optical and semiconducting properties. The strategic integration of both helicity and heteroatoms into the nanographene structure, facilitated by a boron-oxygen-based multiple resonance (MR) thermally activated delayed fluorescence (TADF), elevates its photophysical and chiroptical features. This signifies the introduction of an elegant category of helical nanographene that combines optical (TADF) and chiroptical (CPL) features. In this direction, we report the synthesis, optical, and chiroptical properties of boron, oxygen-doped pi-extended helical nanographene. The pi-extension induces distortion in the DOBNA-incorporated nanographene, endowing a pair of helicenes, (P)-B2NG, and (M)-B2NG exhibiting circularly polarized luminescence with glum of -2.3x10-3 and +2.5x10-3, respectively. B2NG exhibited MR-TADF with a lifetime below 5 mu s, and a reasonably high fluorescence quantum yield (50 %). Our molecular design enriches the optical and chiroptical properties of nanographenes and opens up new opportunities in multidisciplinary fields. B, O-doped pi-extended helical nanographene has been explored for its optical and chiroptical properties. The presence of helical and nanographene segments stabilize the helicity and imparts tunable optical properties. Helical nanographene display circularly polarized thermally activated delayed fluorescence. image
Keywords: circularly polarized luminescence; DOBNA; dual emission; nanographene; TADF